Coaching in education: a professional development process in formation. Issue 1 (1st January 2019) - Lofthouse, Rachel
ABSTRACT: Coaching has been evolving as a form of professional development for teachers and school leaders for several decades, and now exists in many forms. This study focused on the work of six coaches in England, using an adapted focus group approach to discover how they explained and conceptualised the value of their practices. As the coaches' conversations with each other emerged details of the nature of their work, and their reflections on it, were elicited which were analysed thematically while also paying due attention to individual narratives. Although coaching is not easily defined this study demonstrates the significance of relationships and dialogue in coaching and the structures and protocols that support that. It suggests that coaching is suited to helping individuals dealing with authentic challenges, professional interests and dilemmas experienced in complex educational settings, while also acting as a counterweight to some of the consequences of performativity. The study also suggests that coaching may be a valuable means to deploy the expertise of experienced professionals to support an education system exposed to problems of retention of both teachers and school leaders.